Australian company borrowing, 1870-1893: a study in British overseas investment - Bailey, J; J. W. Bailey (1957)
In the last three decades of the nineteenth century British capital played a major part in Australian economic development. The flow of capital to the Australian colonies comprised government borrowing on the one hand, and private borrowing by companies on the other. The present study concerns the flow of capital to the private sector of the Australian economy, most which reached the colonies through the medium of finance companies from the mid 'seventies to 1891. The crux of the study are the new estimates of the annual flow of British capital to the private sector of the Australian economy, excluding mining activity (for which estimates are available), in the 'seventies, 'eighties and 'nineties. Capital reached the colonies through a group of powerful finance companies which employed British capital in the Australian pastoral industry. These companies raised most of their funds in Britain in two ways: first, by issuing short-term debenture bonds, and second, by raising deposits. Debentures were issued by pastoral mortgage and investment companies, and deposits were collected by Australian banks. As the available estimates of this flow of capital are wholly inadequate, the present study contributes a new annual series of Australian company borrowing which was calculated directly from balance-sheets and other data, and not by taking a residual of the balance of payments. In addition, a calculation was made, from 1881 to 1891, on an annual basis, of the total burden of indebtedness of the Australian colonies accruing from government borrowing and this form of company borrowing.